Validation of the energy balance approach for design of vertical lifeline systems. Issue 3 (3rd July 2021) - Lim, Wen Cong; Tashrif, Shazed Mohammad; Goh, Yang Miang; Adrian Koh, Soo Jin
Abstract : To ensure that vertical lifeline systems (VLLSs) are well designed, calculation methods are required to estimate the extension of a personal energy absorber (PEA) ( x PEA ) and the total fall distance ( h TFD ). Thus, the authors conducted 28 tests to validate the accuracy of the energy balance approach for estimating x PEA and h TFD of VLLSs and propose suitable correction factors to improve the accuracy and safety of the estimated x PEA and h TFD . For 9 out of 19 tests with a PEA, the difference between the theorical x PEA and empirical x PEA was 25% or higher, indicating that the energy balance approach is not accurate for estimation of x PEA . In contrast, theoretical values of h TFD are more accurate. Linear regression equations for estimating x PEA ( R 2 = 0.81) and h TFD ( R 2 = 0.99) were developed. The regression equations can be used to improve the accuracy and conservativeness of estimations of x PEA and h TFD during the design of VLLSs.